Homeopathy Seen as Personalised Nanomedicine - Rajendran, E. S. (Homeopathy, 2019)
Among all the discoveries of Hahnemann, potentisation was the most important, though controversial. The curative effect of individualised homeopathic potencies is empirical but inexplicable by the conventional principles of science. This paradox is a highly contentious topic of debate between rationalists and homeopaths. Recent discoveries relating to the nano-particulate nature of homeopathic ultra-high potencies and their potential effect on individual gene expression give new insights into this complex issue. It is concluded that homeopathy may be viewed as ‘personalised nanomedicine’.
Keywords: homeopathy; nanoparticles; potentisation; genetics; personalised nanomedicine